The GEM-handle as convenient labeling strategy for bimodal single-domain antibody-based tracers carrying 99mTc and a near-infrared fluorescent dye for intra-operative decision-making - Declerck, Noemi B.; Huygen, Celine; Mateusiak, Lukasz; Stroet, Marcus C. M.; Hernot, Sophie (Frontiers in Immunology, 2023)
Intra-operative fluorescence imaging has demonstrated its ability to improve tumor lesion identification. However, the limited tissue penetration of the fluorescent signals hinders the detection of deep-lying or occult lesions. Integrating fluorescence imaging with SPECT and/or intra-operative gamma-probing synergistically combines the deep tissue penetration of gamma rays for tumor localization with the precision of fluorescence imaging for precise tumor resection. In this study, we detail the use of a genetically encoded multifunctional handle, henceforth referred to as a GEM-handle, for the development of fluorescent/radioactive bimodal single-domain antibody (sdAb)-based tracers. A sdAb that targets the urokinase plasminogen activator receptor (uPAR) was engineered to carry a GEM-handle containing a carboxy-terminal hexahistidine-tag and cysteine-tag. A two-step labelling strategy was optimized and applied to site-specifically label IRDye800CW and 99m Tc to the sdAb. Bimodal labeling of the sdAbs proved straightforward and successful. 99m Tc activity was however restricted to 18.5 MBq per nmol fluorescently-labeled sdAb to prevent radiobleaching of IRDye800CW without impeding SPECT/CT imaging. Subsequently, the in vivo biodistribution and tumor-targeting capacity of the bimodal tracer were evaluated in uPAR-positive tumor-bearing mice using SPECT/CT and fluorescence imaging. The bimodal sdAb showed expected renal background signals due to tracer clearance, along with slightly elevated non-specific liver signals. Four hours postinjection, both SPECT/CT and fluorescent images achieved satisfactory tumor uptake and contrast, with significantly higher values observed for the anti-uPAR bimodal sdAb compared to a control nontargeting sdAb. In conclusion, the GEM-handle is a convenient method for designing and producing bimodal sdAb-based tracers with adequate in vivo characteristics.